Enhancing Workplace Discipline for Improving Employee Productivity at PT Sumber Bintang Rezeki Bawen - Lurni, Gaudensia Viani; Palupiningtyas, Dyah (Journal of Business Management and Economic Development, 2024)
Human resources play a crucial role in shaping and developing companies, being a vital element for organizational sustainability. The success of a company heavily relies on the presence of talented and outstanding workforce capable of proactively adapting to the dynamics of globalization era. Every individual in the organization has the potential to influence the achievement of organizational goals, and in an increasingly competitive environment, employees must be diligent in their efforts. Quality human resources can be measured through their level of productivity, which is reflected in their ability to efficiently complete tasks and achieve set goals. Efforts to achieve company goals and targets become more easily attainable, and company growth is assured when employees have high levels of productivity. High work productivity helps companies enhance their growth, while less productive employees become impediments to achieving company targets. The company's focus on profitability and meeting the best consumer needs underscores the importance of sustainable work productivity. Employee work productivity becomes crucial as it contributes to the sustainable provision of quality products, thereby enabling the company's profit targets to be achieved. Work productivity, which is a comparison between the results achieved and the resources used, indirectly affects the company's profit achievement. Factors such as employee discipline also influence the level of work productivity, emphasizing the importance of effective human resource management in achieving organizational goals.